El programa de clemencia antimonopolio y sus repercusiones en otros programas de clemencia en Brasil - Athayde, Amanda (2022)
This paper aims to carry out a descriptive analysis of the Antitrust Leniency Program in Brazil, considered the precursor of other Leniency Programs in Brazilian legislation, such as the Anti-Corruption Leniency Program and the Leniency Program in the financial market. First, it is presented a brief historical review of the Program, followed by an explanation of the requirements for signing a Leniency Agreement in Brazil. Second, the paper details all phases of the negotiation process of an Antitrust Leniency Agreement. Finally, it will highlight some of the spillovers of its Program in other fields of Brazilian jurisdiction, with a brief comparison between the different Leniency Programs existent in Brazil in terms of Type of infraction; Competent institution; Legal bases; Infra-legal bases; Possible beneficiaries; Administrative benefits; Criminal benefits and Civil benefits.